HOW CORPORATE GOVERNANCE AND CASH HOLDINGS AFFECT EARNINGS QUALITY AND FIRM VALUE - Lestari, Tri; Hanifah, Imam Abu (TRIKONOMIKA, 2020)
This study analyzes the impact of corporate governance (CG) and cash holdings (CH) on earnings quality and the implication on firm value. We hypothesize that earnings quality mediate the impact of CG and CH on firm value. Banking sector was chosen as the object of research because this sector is quite vulnerable to the global financial crisis. The population consists of banking companies listed on the Indonesia Stock Exchange (IDX) in the period of 2013-2017. Data were analyzed by multiple regression models using SPSS software. The results show that CG and CH have a significant effect on earnings quality. But this influence shows the opposite direction of expectations. Banks with good CG have lower earnings quality, and banks with high CH show better earnings quality. Only CG that has a significant effect on firm value with negative direction. This study did not find the mediating effect from both variables.